2021
DOI: 10.3390/su132312979
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Travel Behaviors to Cope with COVID-19: A Swedish Qualitative Study Focusing on Everyday Leisure Trips

Abstract: The COVID-19 pandemic has caused a rapid change in travel behavior for different types of trips, including everyday social and recreational leisure trips. People have used adaptive travel behaviors to cope with the new circumstances for activities and transport. Due to the Swedish strategy focusing on more voluntary restrictions, people have had reason to consider which trips and activities to skip and which to keep. The overall aim of the study is to explore and deepen the knowledge about adaptive behaviors u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Second, an important observation with huge policyimplications is that around adaptative abilities (Strömblad et al, 2021;Hoolohan et al, 2022). The interviews indeed reveal that people relatively easy adapted to the situation during the pandemic with covid-related restrictions.…”
Section: Concluding Discussion: Any Long-term Lifestyle Transformatio...mentioning
confidence: 89%
See 2 more Smart Citations
“…Second, an important observation with huge policyimplications is that around adaptative abilities (Strömblad et al, 2021;Hoolohan et al, 2022). The interviews indeed reveal that people relatively easy adapted to the situation during the pandemic with covid-related restrictions.…”
Section: Concluding Discussion: Any Long-term Lifestyle Transformatio...mentioning
confidence: 89%
“…Some previous COVID-19 studies observed that people during the lockdowns, faced with a situation of scarcity of socializing, longed for socializing with relatives and friends rather than for material objects (de Haas et al, 2020;Echegaray, 2021;Moynat et al, 2022). Faced with mobility restrictions they longed for freedom in a spatial sense, and they missed activities that were restricted and the possibility to travel various places (Echegaray, 2021;Strömblad et al, 2021;Moynat et al, 2022). However, physical stuff can also be sought for: the pandemic could stimulate a resurgence of hedonistic attitudes connected with phrases such as "I could die tomorrow" or "You only live once" (Zwanka and Buff, 2020).…”
Section: Theoretical Points Of Departure and Thematic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Simma et al [32] studied the destination choice within Switzerland for different activity types. A study on the characteristics of everyday leisure trips for social and recreational purposes was conducted by Strömblad et al [33]. Sener et al [34] studied discretionary leisure activity engagement by children in detail, using data from the United States.…”
Section: Introductionmentioning
confidence: 99%
“…People restructured their daily lives in light of these policies, showing a tendency to reduce their participation in social activities, a shift from public to private transportation and an increase in active mobilities such as walking and cycling (Kolarova et al, 2021; Strömblad et al, 2021). Over time, compliance with NPIs turned the most basic daily movements into a valuable resource to cope with the feeling of being stuck at home (Arroyo et al, 2021; Kellerman, 2022).…”
Section: Introductionmentioning
confidence: 99%